Tinjauan Etis Perspektif Jemaat Terhadap Gaya Hidup Mewah Pendeta Di Jemaat GMIBM Sion Tungoi - Worang, Adinda C. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2021)
The luxurious lifestyle of the pastor in GMIBM Sion Tungoi has led to issues such as distrust, negative perceptions, and a decrease in congregation participation in worship. This situation arises because the pastor's lifestyle is perceived as inconsistent with the values understood in religious teachings, creating doubts about the pastor’s integrity. This study reveals that simplicity is essential for building pastoral integrity. It is crucial for pastors to maintain simplicity and transparency in their service. Meanwhile, congregants should focus on spiritual ministry and avoid being easily influenced by the pastor’s lifestyle. Although a luxurious lifestyle has negative effects, it is important to remember that there are many other factors in evaluating a pastor's suitability, such as teaching abilities, compassion for the congregation, and more.